2014
DOI: 10.1177/2325967114522184
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Injuries During Brazilian Jiu-Jitsu Competition

Abstract: Background:Brazilian jiu-jitsu (BJJ) is a unique style of martial arts with rapid growth in the United States and internationally. Although studies have examined injuries in other martial arts and combat sports, to date, no published medical study has examined injuries in BJJ competitions.Purpose:(1) To estimate the incidence of injuries in BJJ competitions and (2) to identify and describe the types and mechanisms of injuries associated with competitive BJJ.Study Design:Descriptive epidemiology study.Methods:I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 22 publications
3
77
0
7
Order By: Relevance
“…Consistent with our observations, Kreiswirth et al 8 reported a high injury rate during a BJJ World Championship in 2009, particularly at knees (19.4%), shoulders (16.1%) and elbows (19.4%). Scoggin et al 9 while analyzing data from BJJ tournaments in Hawaii from 2005 to 2011 concluded that 19.4% of knee injuries occurred from direct pressure, particularly during passing guard (11.1%). The same authors reported shoulder injuries to be most commonly caused by the kimura technique (joint key in the shoulder).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with our observations, Kreiswirth et al 8 reported a high injury rate during a BJJ World Championship in 2009, particularly at knees (19.4%), shoulders (16.1%) and elbows (19.4%). Scoggin et al 9 while analyzing data from BJJ tournaments in Hawaii from 2005 to 2011 concluded that 19.4% of knee injuries occurred from direct pressure, particularly during passing guard (11.1%). The same authors reported shoulder injuries to be most commonly caused by the kimura technique (joint key in the shoulder).…”
Section: Discussionmentioning
confidence: 99%
“…This scale takes into account training time missed due to injury as a classification of severity as follows: light (with no time lost training), light to moderate (one to two days), moderate (two weeks), moderate to severe (two to four weeks), or severe (four weeks). A similar instrument has been use in previous studies of BJJ athletes 8,9,16,17 .…”
Section: Procedures and Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…6,13 THE KNEE HEEL HOOK INJURY Surprisingly, injuries to the knee while performing a heel hook are also described in martial arts. [14][15][16] In these sports, the factor of velocity adds to the injury impact, which makes it more likely to tear an anterior cruciate than in the more static aspect of the heel hook pull in climbing. Davis et al 16 report 2 cases of high grade lateral collateral ligament injury, 2 in climbing and one in jiu jitsu.…”
Section: The Pelvic Heel Hook Injurymentioning
confidence: 99%